Green Development in Indonesia: Socioeconomic Impacts, Environmental Effects, and the Role of Social Entrepreneurship - Harsono, Iwan (IJBLE Scientific Publications Community Inc., 2024)
The socioeconomic and environmental ramifications of green development in Indonesia are investigated in this study, which also investigates the perspectives of urban residents. The data of 243 participants were analyzed utilizing Structural Equation Modeling (SEM-PLS 4) in a quantitative fashion. The variables comprised perceptions of urban residents, environmental impacts, contributions of social entrepreneurs, and socioeconomic implications. The research findings indicated that green development was regarded favorably, as evidenced by elevated levels of consciousness, perceived significance, and anticipations. Social entrepreneurship has been identified as a substantial mediator in the connection between environmental impacts, socioeconomic ramifications, and perceptions. The implications of the findings extend to policy formulation and urban planning, while also providing significant contributions to the body of literature concerning social entrepreneurship and urban development.